A discourse analysis of the second Aristotelian canon, arrangement, in the selected speeches of Bishop Dumeni (JULACE: Journal of the University of Namibia Language Centre, 2018)
This study investigates arrangement in the speeches of Bishop Kleopas Dumeni. The paper hinges on an Aristotelian theory of rhetoric. Aristotle divides arrangement into the following components, exordium (introduction), narratio (statement of facts), partitio (division), confirmatio (proof), refutatio (refutation) and peroratio (conclusion). These components of arrangement were used to evaluate arrangement in the speech of Bishop Kleopas Dumeni. Bishop Dumeniconducted various speeches calling for the independence of Namibia from 1979 to 1988. However, the speeches of Bishop Dumeni were not subjected to analysis to reveal how his speeches were organised to woo the audience to his side to support him in his decolonising efforts. Content analysis was used to dissect the speeches of Bishop Dumeni to identify the elements of arrangement in these speeches. The study reveals that Bishop Dumeni effectively used the elements of arrangement as expounded in Aristolean theory.
Keywords: Second Aristotelian canon; Bishop Kleopas Dumeni; Aristotelian theory of rhetoric